Pengembangan Model Pembelajaran Berbasis Proyek (PBL) pada Mata Pelajaran Seni dan Budaya Materi Seni Pewarna Alami untuk Meningkatkan Kreativitas Siswa Kelas VI SD N 2 Taman Bali - Wahyu Nurhidayati; Nurul Isnaini Fitriyana (Lembaga Pengembangan Kinerja Dosen, 2026)
. Eco-print is a technique for printing leaf and flower motifs on fabric by utilizing natural materials derived from the surrounding environment. This technique is not only environmentally friendly but also encourages artistic exploration and the sustainable use of natural resources in art education. The method applied in this activity is a project-based learning approach, in which students are actively and collaboratively involved throughout the entire process of artistic creation. The learning stages include the introduction of eco-print concepts, the collection and selection of natural materials, color experimentation, the motif printing process, and the presentation and reflection of the final artworks. The results indicate that students experience improvements in creativity, particularly in imaginative ability, willingness to experiment, problem-solving skills, and aesthetic sensitivity to form and color. In addition, this learning activity contributes to strengthening environmental awareness, care for nature, and the introduction of local wisdom through the use of natural materials. Therefore, the implementation of eco-print and natural dye art has proven to be an effective and innovative learning medium that supports the holistic development of students’ creativity, character, and environmental awareness.